In vitro comparison of the effects of microwave irradiation and chemical and mechanical methods on the disinfection of complete dentures contaminated with Candida albicans - Masoomeh Aslanimehr; Niloofar Mojarad; Safarali Ranjbar; Shima Aalaei (Wolters Kluwer Medknow Publications, 2018)
Background: Dentures can be a source of infection or cross-contamination with microorganisms like Candida albicans. The aim of this in vitro study was to compare the effects of microwave irradiation, chemical techniques, and a mechanical method (i.e., brushing) on the disinfection of complete dentures contaminated with C. albicans. Materials and Methods: In this experimental study, sixty sterilized dentures were divided into six groups of 10 dentures each. The dentures in Groups 1 and 6 served as negative and positive controls, respectively. The dentures (Groups 2-5) were contaminated with C. albicans and subjected to four disinfection procedures: Corega tablets, 2% glutaraldehyde, brushing, and microwave irradiation. Replicate aliquots (25 mL) of the suspension were cultured in Sabouraud dextrose broth. The colonies were counted after 48 h of incubation at 37°C. To confirm long-term disinfection, the Trypticase soy broth (TSB) containers were stored at 37°C for 7 days, and turbidity was visually observed. Data were analyzed with one-way ANOVA and independent-samples t-test on SPSS the level of statistical significance was set at 0.05. Results: The dentures disinfected with microwave irradiation (650 W, 3 min) and glutaraldehyde (2%, 10 min) exhibited no evidence of fungal growth after 48 h of incubation and also no turbidity in the TSB containers after 7 days of incubation. However, the dentures disinfected using the mechanical method and Corega tablets exhibited turbidity after 7 days and fungal growth after 48 h that was significantly more than that in the two other methods (P = 0.000) and less than that in the positive control group (P = 0.000). The differences between mechanical cleaning and cleansing tablet were not significant (P = 0.017). Conclusion: Base on the results of this study, microwave irradiation (650 W, 3 min) and 2% glutaraldehyde completely disinfected the dentures contaminated with C. albicans in the short term and long term.